2015
DOI: 10.1016/j.lungcan.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule targeting of signal transducer and activator of transcription (STAT) 3 to treat non-small cell lung cancer

Abstract: Objective Lung cancer is the leading cause of cancer death in both men and women. Non-small cell lung cancer (NSCLC) has an overall 5-year survival rate of 15%. While aberrant STAT3 activation has previously been observed in NSCLC, the scope of its contribution is uncertain and agents that target STAT3 for treatment are not available clinically. Methods We determined levels of activated STAT3 (STAT3 phosphorylated on Y705, pSTAT3) and the two major isoforms of STAT3 (α and β) in protein extracts of 8 NSCLC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Our results showed an association of combined elevated expression of STAT3 and MUC1 in cancer patient samples with poor chemotherapy response (median overall Our results demonstrated that STAT3 protein is constitutively over-expressed in NSCLC, and could contribute to the regulation of MUC1 mRNA and protein levels. Earlier reports have also indicated the cross-talk of these proteins and have implicated for their functions to promote tumor cell survival [17]. However, the results from -STAT3 and MUC1 knockdown experiments it is evident that -that STAT3 acts at the upstream signaling level and regulate the MUC1 expression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our results showed an association of combined elevated expression of STAT3 and MUC1 in cancer patient samples with poor chemotherapy response (median overall Our results demonstrated that STAT3 protein is constitutively over-expressed in NSCLC, and could contribute to the regulation of MUC1 mRNA and protein levels. Earlier reports have also indicated the cross-talk of these proteins and have implicated for their functions to promote tumor cell survival [17]. However, the results from -STAT3 and MUC1 knockdown experiments it is evident that -that STAT3 acts at the upstream signaling level and regulate the MUC1 expression.…”
Section: Discussionmentioning
confidence: 95%
“…Multiple studies have shown that STAT proteins particularly, STAT3 is abnormally activated in a wide variety of cancer type including NSCLC, and targeting them could provide therapeutic options [12][13][14][15][16][17]. Similarly, MUC1 protein, which is modulated by STAT3 levels, is also indicated to facilitate for tumor survival and progression [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…C188-9 binds to the SH2 domain of STAT3 and blocks its recruitment to the kinase-containing receptor complexes, its tyrosine phosphorylation, and its homodimerization. STAT3 activation can lead to tumorigenesis in diverse type of cancers (18-21). We demonstrated that C188-9 had beneficial effects on both hepatic tumor and NASH in liver, with blockage of tumor growth and progression, prevention of tumor development, reduction of steatosis, inflammation and hepatocellular ballooning, resulting in NASH reversion, and reduction of bile ductular reaction and associated fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a drug development program involving virtual ligand screening, 2-D similarity screening, 3-D pharmacophore analysis, and SAR-based medicinal chemistry, we identified C188-9 as a potent small-molecule that targets the Src-homology (SH) 2 domain of STAT3 (18-21). C188-9 inhibited growth and survival of several cancer cell lines in vitro , including breast cancer (18), acute myeloid leukemia (19), head and neck squamous cell carcinoma (20) and non-small cell lung cancer (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation